Keetsahnak: our missing and murdered Indigenous sisters - Anderson, Kim; Campbell, Maria; Belcourt, Christi (The University of Alberta Press, 2018)
«In Keetsahnak / Our Murdered and Missing Indigenous Sisters, the tension between personal, political, and public action is brought home starkly. This important collective volume both witnesses the significance of the travelling exhibition Walking With Our Sisters and creates a model for antiviolence work from an Indigenous perspective. The contributors look at the roots of violence and how it diminishes life for all. They acknowledge the destruction wrought by colonial violence, and also look at controversial topics such as lateral violence, challenges in working with "tradition," and problematic notions involved in "helping." Through stories of resilience, resistance, and activism, the editors give voice to powerful personal testimony and allow for the creation of knowledge.»-- Provided by publisher.
Keywords: activisme; amériques; anti-violence; approches et analyses; canada; cours; droits des femmes*; droits des femmes* autochtones; féminicide; féminisme autochtone; histoire et politique; intersectionnalité; militance; pol4105; premier cycle; régions géographiques; résistance; système colonial; systèmes d'oppressions; thématiques; violences

Kiffe ta race - Binge Audio - Ly, Grace; Diallo, Rokhaya (Kiffe ta race - Binge Audio, 2018)
Pourquoi le mot « race » est-il tabou ? Qu’en est-il quand on est, à la fois, victime de discriminations raciales et sexuelles ? Comment assumer son identité plurielle ? Un mardi sur deux, Rokhaya Diallo et Grace Ly reçoivent un·e invité·e pour explorer les questions raciales sur le mode de la conversation et du vécu.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; afro-féminisme; approches et analyses; care; com5170; communication; corps; cours; discipline; europe; france; identités; intersectionnalité; journalisme; justice sociale; militance; premier cycle; pédagogie; périodes historiques; racisme; régions géographiques; système colonial; systèmes d'oppressions; thématiques; théorie critique de la race; violences

Whose Land Is It Anyway?: a Manual for Decolonization - McFarlane, Peter; Schabus, Nicole (Federation of Post-Secondary Educators of BC, 2018)
We are pleased to announce the publication of Whose Land Is It Anyway? A Manual for Decolonization; inspired by a 2016 speaking tour by Arthur Manuel, less than a year before his untimely passing in January 2017. The book contains two essays from Manuel, described as the Nelson Mandela of Canada, and essays from renowned Indigenous writers Taiaiake Alfred, Glen Coulthard, Russell Diabo, Beverly Jacobs, Melina Laboucan-Massimo, Kanahus Manuel, Jeffrey McNeil-Seymour, Pamela Palmater, Shiri Pasternak, Nicole Schabus, Senator Murray Sinclair, and Sharon Venne. FPSE is honoured to support this publication.
Keywords: amériques; approches et analyses; canada; cours; féminisme décolonial; histoire et politique; militance; pol4105; premier cycle; racisme; régions géographiques; sexisme; sofia; système colonial; systèmes d'oppressions; thématiques; violences

Danser sur le dos de notre tortue = Niimtoowaad mikinaag gijiying bakonaan: nouvelle émergence des Nishnaabeg - Simpson, Leanne Betasamosake; Régimbald, Anne-Marie (Collection Proses de combat, 2018)
"On parle beaucoup au Québec, comme dans le reste du Canada, de réconciliation avec les Premières Nations. Mais pour qu'un rapprochement fécond puisse avoir lieu, qu'une nouvelle ère, égalitaire et respectueuse, s'ouvre, le cadre constitutionnel canadien ne peut à lui seul en définir les règles. Toute entente devra aussi tenir compte des traditions autochtones. C'est dans ce contexte que le livre de Leanne Simpson trouve toute sa pertinence. L'auteure s'y demande comment redonner force, consistance et valeur à un héritage politique, juridique et culturel mis à mal par le processus colonial. D'une façon aussi concrète que tonique et audacieuse, elle y explore la langue, les mythes, les coutumes et les expériences de sa culture ancestrale afin de recouvrer et révéler cette manière singulière et originale d'être au monde trop longtemps méprisée. Si l'entreprise est inspirante pour toute communauté issue des Premières Nations, elle l'est également pour quiconque s'intéresse aux contradictions de la modernité occidentale."-- Renaud-Bray.
Keywords: amériques; approches et analyses; arts; canada; cours; discipline; féminisme autochtone; histoire et politique; lit3495; militance; ojibwa; premier cycle; premières nations; québec; régions géographiques; système colonial; systèmes d'oppressions; thématiques; violences; études littéraires